2018
DOI: 10.1021/acs.jafc.7b05493
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Induces the Nrf2/HO-1 Antioxidant Pathway in Human Umbilical Vein Endothelial Cells by Generating Trace Amounts of ROS

Abstract: Astaxanthin is a powerful antioxidant that possesses potent protective effects against various human diseases and physiological disorders. However, the mechanisms underlying its antioxidant functions in cells are not fully understood. In the present study, the effects of astaxanthin on reactive oxygen species (ROS) production and antioxidant enzyme activity, as well as mitogen-activated protein kinases (MAPKs), phosphatidylinositol 3-kinase (PI3K)/Akt, and the nuclear factor erythroid 2-related factor 2 (Nrf-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…The former is triggered by FAS, and the latter originates from a release of cytochrome-c. Both pathways are followed by activation of a cascade of caspases [37]. In the present study, CDDP led to apoptosis in both intrinsic and extrinsic pathways, as evidenced by the decreased levels of cleaved caspase 3/9 and cytochrome-c, and the increased expression of BCL-2, which represses apoptosis by blocking the release of cytochrome-c, in accordance with findings from previous studies [38].…”
Section: Discussionsupporting
confidence: 93%
“…The former is triggered by FAS, and the latter originates from a release of cytochrome-c. Both pathways are followed by activation of a cascade of caspases [37]. In the present study, CDDP led to apoptosis in both intrinsic and extrinsic pathways, as evidenced by the decreased levels of cleaved caspase 3/9 and cytochrome-c, and the increased expression of BCL-2, which represses apoptosis by blocking the release of cytochrome-c, in accordance with findings from previous studies [38].…”
Section: Discussionsupporting
confidence: 93%
“…ROS generation acts as a second messenger that triggers keap1 proteolysis and thereby activates Nrf2 signaling [28]. The transcription factor keap1-Nrf2 system interacts with the AREs, leading to the transcriptional activation of anti-oxidant enzymes such as HO-1 [21,32,46]. In the normal state, the cytosolic repressor protein keap1 binds to Nrf2, keeps Nrf2 in the cytoplasm, and promotes its degradation [47].…”
Section: Discussionmentioning
confidence: 99%
“…Increase in intracellular ROS acts as a second messenger to provoke nuclear transcription factors leading to HOMX-1 gene expression to protect against inflammatory responses [20,21]. Our previous study showed that activation of p47 phox / Nox2-dependent ROS generation plays crucial roles in HO-1 expression in HPAEpiCs [19].…”
Section: P47 Phox -Dependent Nox/ros Generation Is Required For Mvs-imentioning
confidence: 99%
See 2 more Smart Citations